O princípio da boa-fé na negociação coletiva trabalhista - Martins, Suzana Leonel (2006)
The purpose of this paper is to studdy the application of the principle of good faith to collective bargaining in Brazilian Law. The study is justified by the importance of collective bargaining as an instrument of pacification of labour conflicts, demanding loyalty and transparency in collective autonomy. The subject is current and important once there is a common sense about the necessity of stimulating collective bargaining instead of seeking all the labour rights from government regulated employment stipulations. Collective bargaining is a way to establish formerly mandated employment conditions and protections, for this reason it needs to gain significance. Collective bargaining is one of the Human Rights, indispensable for the full acomplishment of the dignity of the human being. Good faith is a general principle of Law. There is no duty to bargain in good faith stated by the Brazilian labour law, but it is possible to recognize the general obligation of the parties to conform to the standard of good faith, as it is important for the maintenance of the harmonious development of labour relations. That makes clear the importance of the employers and trade unions negociating in good faith and endeavouring to reach an agreement. The conclusion is that the lack of good faith on collective bargaining may be questioned in the Brazilian Employment Court. In such a case, the Court will reach the best solution to the case, after analysing the facts and circumstances. For instance, the imposition of some penalty on a party that breaches the duty of good faith; a declaration of the nullity of the acts practiced in a breach of good faith; an obligation to refrain from doing something, according to the importance of the action, its consequences and the stage of the collective bargaining